Civil society and the (im)possibilities of algorithmic contestation in migration governance - Eneva, Stoyanka Andreeva; Mora-Gámez, Fredy (Frontiers in Sociology, 2025)
The present article examines the (im)possibilities of contesting algorithmic systems in migration governance through an empirical study of civil society organizations in Sweden and Norway. It draws on qualitative methods including semi-structured interviews, document analysis and digital ethnography to examine how digital rights associations, migrant solidarity initiatives and hybrid groups focused on democratic digitalization respond to the spread of automation in welfare and migration governance. Our findings show an increasing awareness of algorithmic harms but uneven and fragmented capacities for resistance. Digital rights actors prioritize universalist frames of privacy, migrant solidarity groups focus on immediate survival needs, and hybrid organizations emphasize structural barriers to civic contestability. The discussion argues that contestability should be understood not only as a technical property of algorithmic design but also as a socio-political process that requires access to information, shared vocabularies and legitimacy for civic intervention. The study concludes that in high-trust welfare states such as Sweden and Norway, rapid digitalization combined with restrictive migration policies limits the potential for civil society contestation. The study contributes to debates on algorithmic accountability by showing how the Scandinavian experience illustrates both the potential and the limits of civil society contestation in digital governance.